Closing the gender gap in ICT higher education: exploring women’s motivations in pursuing ICT education - Kurti, Erdelina; Ferati, Mexhid; Kalonaityte, Viktorija (Frontiers in Education, 2024)
Rapid development of digital technologies has stemmed profound changes in the society, positioning the ICT sector as a key driver and contributor. This sector, including education, is however characterized by a gender gap, which is problematic in the light of the increasing demand for digital competence and the ability to move towards a sustainable egalitarian society. In this study, we argue for a need to explore the concept of ICT in higher education. This involves assessing the success of educational programs in attracting women and exploring the perceptions of female students regarding their academic environment. With a specific focus on Sweden, through a survey involving 82 respondents, we provide evidence on motivations and perceptions of women regarding leading choices on pursuing ICT higher education. We propose a holistic approach to studying gender representation and inclusion in ICT higher education, with a focus on women's perceptions, experiences, and suggestions.